KOMUNIKASI PERSUASIF AKSI CEPAT TANGGAP (ACT) REGIONAL RIAU DALAM MEMBANTU KORBAN BENCANA ALAM DI INDONESIA MELALUI KEGIATAN PENGGALANGAN BANTUAN - Dika Assyifa Polani; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The occurrence of natural disasters that occur at this time in Indonesia has become awareness and attention for the community to help, the impact that has had an effect on the continuation of the lives of people in the location of the natural disaster. Awareness and sensitivity to social issues can build a person's character about ways of thinking and behaving that help others to live and work together in building a better life (Chrisiana, 2005). Aksi Cepat Tanggap (ACT) Regional Riau is present as a place for distributing aid that makes it easy for the community to donate and be trusted as well as trust. ACT has a disaster emergency program, which handles problems related to events to natural disasters that occur. In the implementation of the program, persuasive communication is carried out so that the people who become the goals can act as expected. The purpose of this study was to determine the credibility of persuaders, persuasive messages, and communication media in the ACT-funded relief activities for victims of natural disasters that occurred in Indonesia.This study uses a qualitative descriptive research method. The technique of determining research informants using purposive sampling techniques. The informants in this study were ACT Riau Regionalh leader, four ACT Riau administrators, two permanent donors, and one non-permanent donator from ACT Riau. Data collection techniques carried out were interviews, observation, documentation. The validity of the data in this study the author uses an extension of participation and triangulation.The results of the study show that ACT Riau has credibility as a persuader formed from aspects of expertise through experience and mastery of information delivered based on the facts of natural disaster conditions. The persuasive message delivered consists of verbal messages including simple message clarity, message misunderstanding that is easily remembered by the community, and the accuracy of the message objectives in providing information regarding natural disasters that hit a region. Whereas nonverbal messages are seen from facial expressions, intonation, ethics, to the use of attributes as ACT identities. The selection of media consists of Instagram social media, Facebook and print media in the form of banners, billboards, and flayer which are placed in locations where many people pass through.Key Words: Persuasive Communication, Aksi Cepat Tanggap, Persuasive Communication Model of Applebeum & Anatol.